2019
DOI: 10.3389/fphys.2019.01289
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Analysis of the Stress and Immune Response Genes to Temperature Stress in Ostrinia furnacalis

Abstract: Ostrinia furnacalis is one of the most important pests on maize. O. furnacalis larvae are frequently exposed to the temperature challenges such as high temperature in summer and cold temperature in winter in the natural environment. High and low temperature stress, like any abiotic stress, impairs the physiology and development of insects. Up to now, there is limited information about gene regulation and signaling pathways related to the high and cold stress response in O. furnacalis. High-throughput sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 59 publications
3
23
1
Order By: Relevance
“…However, the precise functions of OBP genes in the insect fat body, Malpighian tubule, and hemolymph is unknown. Coincidentally, these tissues are involved in metabolic detoxification in insects ( Beyenbach et al, 2010 ; Chen K. et al, 2019 ; Li et al, 2019 ). Therefore, we speculate that TcOBPC11 in T. castaneum could play an important role in the degradation of exogenous substances.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise functions of OBP genes in the insect fat body, Malpighian tubule, and hemolymph is unknown. Coincidentally, these tissues are involved in metabolic detoxification in insects ( Beyenbach et al, 2010 ; Chen K. et al, 2019 ; Li et al, 2019 ). Therefore, we speculate that TcOBPC11 in T. castaneum could play an important role in the degradation of exogenous substances.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that a short exposure of G. mellonella to low temperatures led to an increase in AMP expression in response to B. thuringiensis infection [ 28 ]. Similar exposure led to enhanced AMP expression in Ostrinia furnacalis in the absence of infection [ 29 ]. Elevated antibacterial responses were also observed under prolonged cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Insect antibacterial responses are also dependent on environmental temperatures [ 25 , 26 , 27 ] and elevated temperature often promotes bacterial infection [ 16 , 17 ]. There are examples of increased antibacterial responses in insects under short-term or prolonged exposure to low temperatures [ 16 , 26 , 28 , 29 ]. Importantly, in a state of cold diapause, cellular immunity continues to work [ 30 ] and changes in microbiome composition, immune response and susceptibility to fungal and bacterial infections may also occur [ 27 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of cold tolerance in insects have focused on the determination of the supercooling point, survival in low-temperature conditions, the cold tolerance index, and the influence of cold acclimation on insect biology. Transcriptome techniques, such as gene chip technology, expressed sequence tags, serial analysis of gene expression, and RNA sequencing, have been used to identify highly expressed cold-related genes in insects ( Barth et al, 2018 ; Chen et al, 2019 ; Enriquez & Colinet, 2019 ). To screen cold-tolerant genes, a variety of tools for studying differential gene expression are available, including cDNA library screening, suppression subtractive hybridization, and microarray screening ( Parker et al, 2018 ; Martinson et al, 2019 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%